2020
DOI: 10.1038/s41746-020-0273-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated abnormality classification of chest radiographs using deep convolutional neural networks

Abstract: As one of the most ubiquitous diagnostic imaging tests in medical practice, chest radiography requires timely reporting of potential findings and diagnosis of diseases in the images. Automated, fast, and reliable detection of diseases based on chest radiography is a critical step in radiology workflow. In this work, we developed and evaluated various deep convolutional neural networks (CNN) for differentiating between normal and abnormal frontal chest radiographs, in order to help alert radiologists and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(118 citation statements)
references
References 33 publications
1
116
0
1
Order By: Relevance
“…Tang et al [41] exploited a unique technique to train and evaluate their pneumonia detection model. They first trained their GoogleNet based model on the large NIH dataset of [26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [41] exploited a unique technique to train and evaluate their pneumonia detection model. They first trained their GoogleNet based model on the large NIH dataset of [26].…”
Section: Related Workmentioning
confidence: 99%
“…All the past models [7,[20][21][22][23][24][38][39][40][41], except [43], have been evaluated in terms of only performance and not in terms of efficiency. Unlike other related work, Hu et al [43] have worked on model efficiency rather than just accuracy.…”
Section: Pneumonianet's Efficiencymentioning
confidence: 99%
“…Mostly built on convolutional neural networks (CNNs), the algorithms can detect certain pulmonary abnormalities in CXR images within a second. Numerous studies have shown the competency of CNNs achieving performance close to radiology experts 7,11,12,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The advances in terms of computational capabilities as well as the availability of large labeled datasets have promoted the use of deep learning techniques in the field of medical imaging [15]. In particular, the potential of these techniques has been exploited for the detection and assessment of cardiothoracic and pulmonary abnormalities in chest X-ray imaging, one of the most widely used imaging tests in medical practice [16] [17]. Therefore, Anthimopoulos et al [18] present a deep CNN (Convolutional Neural Network) to classify lung image patches into 7 categories considering 6 different patterns of interstitial lung diseases as well as healthy tissue.…”
Section: Introductionmentioning
confidence: 99%